TINJAUAN YURIDIS TERHADAP PUTUSAN PENGADILAN AGAMA PEKANBARU TERHADAP PERCERAIAN TANPA IKRAR TALAK (Studi Putusan Nomor : 0600/Pdt.G/2015/PA.Pbr) - Nurlia '; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Article 1 of Law Number 1 Year 1974 Concerning Marriage affirms,marriage is the inner birth bond between a man and a woman as husband andwife, with the aim of forming a happy and eternal family (household) based on thedivinity of the One Supreme. However, maintaining a household is not easy. Thebreakup of marriage for three reasons, namely divorce, death and court decisions.Literally, talak means freelance and freedom. Divorce divided again that is,divorce raj'i or divorce 1, may refer before the iddah ends. Divorce ba'in small ordivorce 2 which in the sense can still be re-referenced, and divorce ba; in sughratalak 3 can not return before ex-wife married to another man and divorced.The consideration of the judges of the Religious Courts of Pekanbaru inhandling divorce cases without the pledge of divorce which the authors obtainedfrom the copy of number 0600 / Pdt.G / 2015 / PA.Pr., Is the verdict of the trial ofthe pledge of divorce between the applicant, Efendi bin Zahar Labai with theRespondent Neli Ernawati bint Syahril. Whereas in the rule of Islamic law if therequirements of divorce are fulfilled then divorce has been considered fallen. Inthis case Efendi bin Zahar Labai and Neli Ernawati bint Syahril have been legallydivorced according to Islam but there is still a legitimate marriage bond betweenthem. According to a positive judicial review, the judges consider no divorcebetween the applicant and the requested party, as the appellant of therepresentative / his proxy does not come to the pledge of divorce even afterexceeding the 6 (six) month period. According to the authors this does not givecertainty to the petitioners for their status, their divorce is not legitimate in theeyes of law because divorce is considered lawful if it has been decided by thecompetent court and also executed in accordance with the applicable law, butaccording to Islamic Shari'a still has fall of divorce to wife.Keywords: Divorce_ Pledge of Talak